Synthesis and characterization and biological evaluation of bivalent metal complexes with (E)-4-bromo-N'-(4-chlorobenzylidene) benzohydrazide ligand - Abdullah, Khalid Tuama; Etheb, Alaa Mohammed; Majeed, Wedad Hameed; Al-Janabi, Ahmed S.M.; Hussien, Nasry Jassim (Edelweiss Applied Science and Technology, 2025)
New (E)-4-bromo-N'-(4-chlorobenzylidene)benzohydrazide (BrphOH) complexes of some bivalent metal ion complexes were synthesized and analyzed through microelemental investigation, infrared spectroscopy, conductivity measurements, and 1H NMR spectroscopy. The BrphOH was bonded with the M(II) as a chelating ligand through the oxygen atom of the carbonyl group and the nitrogen atom of the azomethine group to afford octahedral complexes of the formula [MCl2(BrphOH)(H2O)2] {MII = Co (1), Ni (2), and Cu (3)}, or as a square planar complex of the type [PdCl2(BrphOH)](4), or as tetrahedral complexes of the formula [MCl2(BrphOH)] (MII = Zn (5), Cd (6), and Hg (7)). The prepared complexes were screened against Chlamydia trachomatis, Bacillus subtilis, Nosocomiicoccus ampullae, and Escherichia coli. The Palladium (II) and Nickel (II) complexes presented more advanced microbial action than the other compounds.